A phonetico-semantic analysis of verb-noun contractions in Yoruba - B. Rotimi Badejo (LibraryPress@UF, 1986)
This paper highlights the various studies which have been carried out to determine the rules which govern the elision of one of the vowels in a verb-noun concatenation where the verb is vowel-final and the noun vowel-initial. It proposes that there are basically three phonological rules which come into play at the Deep Structure Level. However, at the Surface Structure Level, the paper recognizes that there is a Semantic Dissimilation Principle (SDP), which may block the application of otherwise well-motivated rules. The SDP, then, guarantees maximal perceptual distance between otherwise homophonous products of the phonological rules.